Referral routes to hospital of patients with chronic open-angle glaucoma. Issue 6348 (16th October 1982) - MacKean, J M; Elkington, A R
Abstract : An analysis of the referral routes of Southampton Eye Hospital of 191 patients who had been diagnosed as having chronic open-angle glaucoma showed that 121 patients (63.4%) were diagnosed as a result of the patient seeking advice for ocular symptoms (118) or because they had a family history of glaucoma (3). Advice had been sought from general practitioners (48), ophthalmic medical practitioners (19), and ophthalmic opticians (46). The remaining eight patients had gone directly to the casualty department. Seventy patients had been identified by chance, the majority of ophthalmic medical practitioners (26) or ophthalmic opticians (32).